Assessing why the increased capitalist global trading environment is under pressure: What are the prospects for more stability returning in the near future?. (15th November 2020) - Floyd, David
Abstract: The global business environment has been hit by multiple shocks in a short space of time, leading to an increased risk of protectionism. More rather than less global cooperation is needed.